Pengaruh PPKM terhadap Minat Wisatawan untuk Berkunjung Ke Destinasi Wisata Salib Kasih Tarutung - Apriliani Lase; Apriliana Lase; Angelia Putriana; Siti Aisyah; Sabam Syahputra (TOBA: Journal of Tourism, Hospitality, and Destination, 2023)
The implementation of Community Activity Restrictions (PPKM) as an effort to control the COVID-19 pandemic has had a significant impact on various sectors, including tourism. This study aims to analyze the effect of PPKM on tourists' interest in visiting the Salib Kasih Tarutung tourist destination. This study uses a quantitative approach by distributing questionnaires to 100 respondents who have visited Salib Kasih Tarutung before and during the PPKM period. Data were analyzed using descriptive statistical tests and simple linear regression. The results showed that there was a decrease in tourists' interest in visiting Salib Kasih Tarutung during the PPKM period. Factors such as mobility restrictions, concerns about virus transmission, and decreased income were the main causes of the decline in interest. However, some tourists still showed interest in visiting by paying attention to strict health protocols. This research provides important implications for tourist destination managers and related stakeholders to develop adaptive strategies in dealing with pandemic situations. It is important to increase tourism promotion that focuses on the safety and comfort of tourists, as well as provide facilities and services that comply with health protocols. In addition, collaboration between the government, tourist destination managers, and the local community is also needed to restore the tourism sector after PPKM.